Poly(vinylidene fluoride-co-hexafluoropropylene)/polyaniline blends assisted by phosphonium – Based ionic liquid: Dielectric properties and β-phase formation. (December 2015) - Soares, Bluma G.; Pontes, Ketly; Marins, Jéssica A.; Calheiros, Loan F.; Livi, Sébastien; Barra, Guilherme M.O.
Graphical abstract: Highlights: Ionic liquid increases conductivity of PVDF-co-HFP/polyaniline blends. The formation of β-crystalline phase of PVDF-co-HFP was enhanced. Higher EMI shielding effectiveness was reached for blends containing ionic liquid. Abstract: In this paper, the ionic liquid denoted tributyl(tetradecyl)phosphonium dodecylbenzenesulfonate (IL) was used for the first time to improve the processability of blends based on polyaniline and a fluorinated polymer matrix during the melting process. In this case, polymer blends constituted by poly(vinylidene fluoride)-co-(hexafluoropropylene) (PVDF-co-HFP) and polyaniline doped with dodecylbenzene sulfonic acid (PAni.DBSA) were prepared at different compositions with the presence of IL. Thus, the use of 5 wt% of IL exerts a strong influence on the melt viscosity, mainly for blends containing 10 wt% of PAni.DBSA. In addition, improved electrical conductivity and dielectric properties (permittivity and dielectric loss), as well as electromagnetic interference shielding effectiveness (EMI SE) in the X-band frequency range are achieved by adding IL to the conducting blends. The presence of IL favors the formation of conducting pathways of PAni.DBSA in the thermoplastic matrix as observed by scanning electron microscopy (SEM). Moreover, the β-crystalline phase fraction of PVDF–HFP is significantly enhanced by the presence of IL, as indicated by X-ray diffraction.